Coping strategies, concerns, and habits of Brazilian men in the COVID-19 context - Anderson Reis de Sousa; Jules Ramon Brito Teixeira; Tilson Nunes Mota; Thiago da Silva Santana; Sélton Diniz dos Santos; Magno Conceição das Merces; Evanilda Souza de Santana Carvalho; Álvaro Francisco Lopes Sousa (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To describe coping strategies, concerns and habits of Brazilian men during the COVID-19 pandemic. Method: Cross-sectional, descriptive and nationwide study, carried out in 2020 with a total of 1015 men living in Brazil. A descriptive statistic was used. Results: Young (41.2%), black (61.4%), highly educated (66.8%), high income (33.2%), living with family/friends (49.7%) and formal workers (65.6%) predominated. As coping strategies predominated: exclusive use of the private health system (36.4%), support from family/friends (78.2%) and leisure (97.7%) and domestic activities (64.9 %). Social distancing (59.7%), economic (58.0%) and work situations (44.4%) were the main reasons for concern. Among the prevention/control attitudes, hand washing (94.3%) and social distancing (91.0%) prevailed. Media consumption (84.6%) and health risk (65.4%) were the main increased habits. Conclusion: Brazilian men adopted coping strategies recommended by health authorities, with concerns and habits of potential risk to physical and mental health.